METAL CORROSION IN WATERBORNE PRESERVATIVE- TREATED WOOD - Krisdianto Sugiyanto; Didik A. Sudika (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2010)
The rigidity and firmness of wooden construction and furniture those are joined by metal screws depend on corrosion rate of these metals. This paper examines the weight-loss percentage of metal screws used in wood samples that have been treated with water-borne preser vative (i.e.3% borax boric acid and 3% diffusol CB) and concurrently investigates the effect of brake fluid on preventing metal corrosion. Wood samples tested included three acacia and one eucalypts wood species which were grouped into sapwood and heartwood containing samples. Wood samples fastened with metal screws were freely suspended in glass jars that contained 25 ml of sulphuric acid (H2SO4) to keep the humidity rate above 90%. After 12 months, the metal screws lost their weight due to the corrosion brought about by the related factors either in separate individual or in combination, which comprised brake and fluid-dipping , wood species, wood portion (sapwood and heartwood), kinds of preser vatives used. Corrosion rates of metal screws fastened in eucalypts wood sample as indicated by the screw-weight loss (i.e. 5.8%) was more severe than that fastened in acacia wood. Furthermore, corrosion rate of metal screws as fixed firmly in sapwood sample proceeded faster than that in heartwood. This might be caused by the higher moisture content in sapwood. On the other hand, corrosion rate of the screws as fastened in waterborne-preser vative-treated wood samples was greater than that in non-preser ved wood due to electrokinetic characteristics and ionic potential exhibited by the preser vative thereby intensif ying the screw-corrosion process. Meanwhile, less severe corrosion was obser ved and recorded on the screws pre-dipped in brake fluid compared to those on the non-dipped screws